FinTech as a driver for today’s financial market transformations: the Ukrainian context - Нікіфоров, Петро (My University, 2020)
The article analyzes the impact of the FinTech sector on transformation processes in the financial markets. Modern transformations of the financial market are connected with the emergence of new financial instruments and financial service providers on the basis of accelerated development of digital financial technologies. In today's environment, the Internet has become widespread, smartphones, mobile applications and social networks are rapidly expanding and gaining popularity, existing IT companies are developing innovative products and services that are setting new standards for consumers, businesses are looking for alternative sources of finance. There is a combination of finance and the latest technologies and the emergence of non-traditional financial institutions of FinTech companies. The most popular area of work in FinTech in Ukraine is payments and software development for the financial sector. The FinTech sector has tremendous transformational power for the financial markets, but it also causes new risks, especially in marketing discourse. Overcoming such risks also requires institutional change. Finding new marketing opportunities by the financial business and focusing on competitive strategies makes FinTech a major driver of transformation in the financial markets.
FINTECH ЯК ДРАЙВЕР СУЧАСНИХ ТРАНСФОРМАЦІЙ ФІНАНСОВИХ РИНКІВ: УКРАЇНСЬКИЙ КОНТЕКСТ
Keywords: financial technologies; financial innovations; FinTech-companies; institutional transformations,; financial markets; card payments; software products